What alternatives for regional development? Borders, potentialities and territorial vocations (Revista LIDER, 2020)
We propose a reflection about of development achieved in the local’s territories by analyzing the “border” and “limit” notions, in both case indissoluble devices for to territorial characteristics. We assume the regions have been designed as politics and administrative spaces and socially defined, but it is essential to boost the territorial component to achieve a more assertive analysis in the intervention strategy. Territory represents and recreating cultural individual identities, but which in turning represents a space where intervene from identify their common characteristics, but also their unequal conditions of development and resources available. In this sense, would you considered regionalization as a catalyst to detonate opportunities and thereby achieve transcendental purposes? The response you want to give means to think in regional as a possibility for development if it is capable of combining the platform features of land that are expressed from the economic activities that develop and that could be developed in these territories (vocations) and on the conditions and natural characteristics that define the regions in the singular and in particular (potential).